Volatile Organic Compound in the Environment: Sources, Exposure and Mitigation - Abakpa, A.M.; Japhet, T; Omale, Precious; Chiyam, BB; Peter, Inedu; Abu, Grace Otinu (Darul Yasin Al Sys, 2024)
Volatile Organic Compounds (VOCs) constitute a diverse group of carbon-based chemicals that vaporize under normal environmental conditions. Their ubiquitous presence in the environment arises from both natural and anthropogenic sources, including industrial processes, vehicle emissions, and biological activities. This review explores the sources, exposure pathways, and mitigation strategies associated with VOCs in the environment. Anthropogenic activities such as transportation, manufacturing, and solvent use are significant contributors to VOC emissions, leading to concerns about their impact on air quality and human health. Exposure to VOCs occurs through inhalation, ingestion, and dermal contact, with potential health effects ranging from respiratory irritation to long-term risks such as cancer and neurological disorders. The application of nanomaterials in VOC reduction has encouraging opportunities to improve the effectiveness of environmental pollutant removal. Future research directions should focus on advancing monitoring technologies, assessing the efficacy of mitigation strategies, and understanding the complex interactions between VOCs and environmental factors.